Praktek Kecurangan (Fraud) dan Modusnya di Lingkungan Usaha PT JOY - Safuan Safuan; M. Azmi Lesmana (MAKSIMUM: Media Akuntansi Universitas Muhammadiyah Semarang, 2021)
This research was conducted to determine whether there was fraud that occurred in the PT JOY business environment, the types of fraud and the modes of fraud carried out by individual employees.  The method used in this research is a qualitative approach, with a case study.  Most of the fraud committed by unscrupulous employees in the PT JOY business environment occurs due to weak systems and lack of supervision from company management. The author hopes that the results of the research will be used as material for evaluating management systems and policies because if proven, of course this fraud will cause a large potential loss for the company.